A novel mouse model for colitis-associated colon carcinogenesis induced by 1,2-dimethylhydrazine and dextran sulfate sodium - Wang, Jian-Guo (World J Gastroenterol, 2004)
AIM: To develop an efficient animal colitis-associated carcinogenesis model and to detect the expression of β -catenin and p53 in this new model. METHODS: Dysplasia and cancer were investigated in mice pretreated with a single intraperitoneal injection of 20 mg/kg body mass of 1,2-dimethylhydrazine prior to three repetitive oral administrations of 30 g/L dextran sulfate sodium to give conditions similar to the clinically observed active and remission phases. Immunohistochemical staining of β - catenin and p53 was performed on paraffin-imbedded specimens of animals with cancer and/or dysplasia, those without dysplasia and the normal control animals. RESULTS: At wk 11, four early-invasive adenocarcinomas and 36 dysplasia were found in 10 (90.9%) of the 11 mice that underwent 1,2-dimethylhydrazine-pretreatment with 3 cycles of 30 g/L dextran sulfate sodium-exposure. Dysplasia and/or cancer occurred as flat lesions or as dysplasia-associated lesion or mass (DALM) as observed in humans. Colorectal carcinogenesis occurred primarily on the distal portion of the large intestine. No dysplasia and/or cancer lesion was observed in the control groups with 1,2-dimethylhydrazine pretreatment or 3 cycles of 30 g/L dextran sulfate sodium exposure alone. Immunohistochemical investigation revealed that β -catenin was translocated from cell membrane to cytoplasm and/or nucleus in 100% of cases with dysplasia and neoplasm, while normal membrane staining was observed in cases without dysplasia and the normal control animals. Nuclear expression of p53 was not detected in specimens. CONCLUSION: A single dose of procarcinogen followed by induction of chronic ulcerative colitis results in a high incidence of colorectal dysplasia and cancer. Abnormal expression of β -catenin occurs frequently in dysplasia and cancer. This novel mouse model may provide an excellent vehicle for studying colitis-related colon carcinogenesis.